2015
DOI: 10.2174/1573397111666150522094716
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant- Antioxidant Balance (PAB) in Rheumatoid Arthritis and its Relationship to Disease Activity

Abstract: The PAB test can show the oxidative stress in RA patients. Further research should be done to determine the potency of the PAB assay as a tool for monitoring adverse effect of oxidative stress in RA, as well as the effect of antioxidant therapies in the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…37,38) Oxidative stress is involved in the pathogenesis of RA. 5) ROS degrade proteoglycans, activate metalloproteinases, and induce apoptosis of chondrocytes, contributing to the damage to cartilage and bone tissue. 39) We demonstrated that OLM reduced MDA levels in the synovium of rats, reflecting an improvement in lipid peroxidation, and increased levels of GSH, an impor- The experimental groups were saline only, zymosan only (Zy), olmesartan (OLM) 15 and 30 mg/kg, and diclofenac sodium (SD) 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38) Oxidative stress is involved in the pathogenesis of RA. 5) ROS degrade proteoglycans, activate metalloproteinases, and induce apoptosis of chondrocytes, contributing to the damage to cartilage and bone tissue. 39) We demonstrated that OLM reduced MDA levels in the synovium of rats, reflecting an improvement in lipid peroxidation, and increased levels of GSH, an impor- The experimental groups were saline only, zymosan only (Zy), olmesartan (OLM) 15 and 30 mg/kg, and diclofenac sodium (SD) 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA have high oxidative stress levels and higher malonaldehyde (MDA) levels than do normal patients. 5) Data suggest that an antioxidant diet can reduce RA incidence. 6) RA is considered to be a systemic disease that primarily affects the joints, but inflammatory mediators involved in the pathogenesis of the disease can affect other organs, such as the heart.…”
mentioning
confidence: 99%
“…A modified PAB was applied based on a previously described method. 13,14 The standard solutions were prepared by mixing varying proportions (0–100%) of 250 µM hydrogen peroxide with 3 mM uric acid (in 10 mM sodium hydroxide). Sixty milligrams of tetramethylbenzidine (TMB) powder was dissolved in 10 mL dimethyl sulphoxide (DMSO); for the preparation of TMB cation, 400 µL of TMB/DMSO was added to 20 mL of acetate buffer (0.05 M buffer, pH 4.5), and then 70 µL of fresh chloramine T (100 mM) solution was added to this 20 mL, mixed well, incubated for 2 hours at room temperature in a dark place; 25 U of peroxidase enzyme solution was added to 20 mL TMB cation, dispensed in 1 mL and kept at 20℃.…”
Section: Methodsmentioning
confidence: 99%
“…Основний ушкоджуючий механізм вільних радикалів полягає в руйнуванні мембран клітин, модифікації білків та ДНК шляхом перекисного окиснення ліпідів (ПОЛ). Високий рівень ПОЛ сприяє апоптозу кардіоміоцитів і відіграє важливу роль в ремоделюванні міокарда, та розвитку діастолічної дисфункції [3,4,5].…”
Section: зв'язок маркерів оксидативного стресу з діастолічною функцієunclassified